Centralised solar charging station for LED lanterns for deployment in Indian rural areas: a design approach. (2016) - Sharma, K. Rahul; Thakur, Nivedita; Sharma, Arvind; Mohanty, Parimita
With the ever improving lighting and photovoltaic industries and the initiatives of various solar lighting programs, the market is witnessing a gamut of solar lighting products and delivery models for the same. Besides the widely used stand-alone model, the lighting services of solar lanterns and other portable solar lighting products can be alternatively delivered through charging station models; especially catering to the populace who are unable to purchase standalone models. This paper presents an approach towards designing a central charging station model for solar LED lanterns for rural areas considering the various climatic conditions throughout India, the available technology and the field dynamics. Theoretical design based on the available climatic data is presented followed by the experimental observation at a typical site in one climatic zone as a case. The paper concludes with a discussion on the way-forward towards design and operation improvements for this present model.